Construct Validity of Cognitive Reserve in a Multi-Ethnic Cohort: the Northern Manhattan Study - Siedlecki, Karen L. (2009)
Cognitive reserve is a hypothetical construct that has been used to inform models of cognitive aging, and is presumed to be indicative of life experiences that may mitigate the effects of brain pathology. The purpose of this study was to evaluate the construct validity of cognitive reserve by examining both its convergent and discriminant validity across three different samples of participants using structural equation modeling. The cognitive reserve variables were found to correlate highly with one another (thereby providing evidence of convergent validity) but demanding tests of discriminant validity indicated that, in two of the samples, the cognitive reserve construct was highly related to an executive functioning construct.